Management accounting control system and risk governance in public sector organizational resilience enhancement - Quang Huy Pham; Kien Phuc Vu (Cogent Social Sciences)
This research seeks to examine the influence of the integration of management accounting control systems and risk governance (MACS-RG) on organizational resilience (OR) in public sector organizations (PSO). This investigation endeavors to offer critical insights in the enhancement of OR in the PSO by investigating the components of MACS-RG. The authors employ a two-phase methodology, incorporating both qualitative (Study 1) and quantitative (Study 2) approaches. The authors utilize qualitative research to reveal significant insights and develop a framework, which is later evaluated in the quantitative phase. The research results shed light on the significantly positive relationships among various components of MACS-RG, including continuous planning, internal control, increasing network with external stakeholders, performance measurement, risk management, with OR enhancement. The study holds important implications for managers, researchers, and individuals engaged in the making, implementing, or evaluating of decisions pertaining to the enhancement of OR via MACS-RG. The paper will delineate the strategic interventions necessary for the effective MACS-RG within the PSO context.